Accountability Analysis of High Leadership Positions for ASN Pratama Tolitoli District - Fiansi Fiansi (Universitas Muhammadiyah Palu, 2022)
Open selection is a relevant structural position filling mechanism based on the value of accountability and a merit system. Based on Law Number 5 of 2014 concerning State Civil Apparatus, which requires filling the Primary High Leader Position using the system. His study aims to analyze the mechanism for implementing an open selection, commonly called an auction of positions, in procedural accountability for the Primary High Leadership Position of ASN Tolitoli Regency. The approach in this research is qualitative with descriptive analysis. With the method of collecting interview data and documentation. Research results in bidding for positions, the procedural accountability criteria have been met because the applicable requirements and provisions carried out each stage by Law Number 5 of 2014 concerning State Civil Apparatus.